Whole transcriptomic analysis of mesenchymal stem cells cultured in Nichoid micro-scaffolds - Testa, Carolina; Oliveto, Stefania; Jacchetti, Emanuela; Donnaloja, Francesca; Martinelli, Chiara; Pinoli, Pietro; Osellame, Roberto; Cerullo, Giulio; Ceri, Stefano; Biffo, Stefano; Raimondi, Manuela T. (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stem cells (MSCs) are known to be ideal candidates for clinical applications where not only regenerative potential but also immunomodulation ability is fundamental. Over the last years, increasing efforts have been put into the design and fabrication of 3D synthetic niches, conceived to emulate the native tissue microenvironment and aiming at efficiently controlling the MSC phenotype in vitro. In this panorama, our group patented an engineered microstructured scaffold, called Nichoid. It is fabricated through two-photon polymerization, a technique enabling the creation of 3D structures with control of scaffold geometry at the cell level and spatial resolution beyond the diffraction limit, down to 100 nm. The Nichoid’s capacity to maintain higher levels of stemness as compared to 2D substrates, with no need for adding exogenous soluble factors, has already been demonstrated in MSCs, neural precursors, and murine embryonic stem cells. In this work, we evaluated how three-dimensionality can influence the whole gene expression profile in rat MSCs. Our results show that at only 4 days from cell seeding, gene activation is affected in a significant way, since 654 genes appear to be differentially expressed (392 upregulated and 262 downregulated) between cells cultured in 3D Nichoids and in 2D controls. The functional enrichment analysis shows that differentially expressed genes are mainly enriched in pathways related to the actin cytoskeleton, extracellular matrix (ECM), and, in particular, cell adhesion molecules (CAMs), thus confirming the important role of cell morphology and adhesions in determining the MSC phenotype. In conclusion, our results suggest that the Nichoid, thanks to its exclusive architecture and 3D cell adhesion properties, is not only a useful tool for governing cell stemness but could also be a means for controlling immune-related MSC features specifically involved in cell migration.